Physical Activity, Body Mass Index, and Blood Progranulin in Older Adults: Cross-Sectional Associations in the MAPT Study. Issue 6 (17th January 2022) - Raffin, Jérémy; Angioni, Davide; Giudici, Kelly V; Valet, Philippe; Aggarwal, Geetika; Nguyen, Andrew D; Morley, John E; Guyonnet, Sophie; Rolland, Yves; Vellas, Bruno; de Souto Barreto, Philipe; ,
Abstract: Physical activity (PA) has been shown to moderate the negative effects of obesity on pro-inflammatory cytokines but its relationship with the adipokine progranulin (PGRN) remains poorly investigated. This study aimed to examine the cross-sectional main and interactive associations of body mass index (BMI) and PA level with circulating PGRN in older adults. Five-hundred and twelve participants aged 70 years and older involved in the Multidomain Alzheimer Preventive Trial (MAPT) study who underwent plasma PGRN measurements (ng/mL) were included. Self-reported PA levels were assessed using questionnaires. People were classified into 3 BMI categories: normal weight, overweight, or obesity. Further categorization using PA tertiles was used to define highly active, moderately active, and low active individuals. Multiple linear regressions were performed in order to test the associations of BMI, PA level, and their interaction with PGRN levels. Multiple linear regressions adjusted by age, sex, diabetes mellitus status, total cholesterol, creatinine level, and MAPT group demonstrated significant interactive associations of BMI status and continuous PA such that in people without obesity, higher PA levels were associated with lower PGRN concentrations, while an opposite pattern was found in individuals with obesity. In addition, continuous BMI was positively associated with circulating PGRN in highly active individuals but not in their less active peers. This cross-sectional study demonstrated reverse patterns in older adults with obesity compared to those without obesity regarding the relationships between PA and PGRN levels. Longitudinal and experimental investigations are required to understand the mechanisms that underlie the present findings. Clinical Trials Registration Number: NCT00672685